Die ongelooflike avonture van Afrikaanse filmaanpassings: filmic adaptations of Afrikaans literature with specific focus on novels, youth literature and stage plays - Du Plooy, Alta (Centre for Film and Media Studies, 2015)
Includes bibliographical references.